The Value of Character Education In Bird's Of Prey Films - Zulpahmi; Rapi Renda; Taufik Mawardi (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2025)
The purpose of this study is to find out the results of the semiotic analysis of the message of women's emancipation contained in the film Birds of Prey using Roland Barthes' semiotics approach. The data collection technique in this study uses documentation sourced from primary data in the movie Birds of Prey. The analysis technique uses Roland Barthes' qualitative descriptive theory and semiotics, and the use of post-feminist theory. Taking the subject refers to the figure of Harley Quinn by looking through denotative terms that explain the relationship between the marker and the marker in reality, resulting in an explicit meaning. Connotations explain the relationship of markers and markers with non-reality, generating implicit meanings and myths explaining the customs and beliefs that prevail in society. The analysis shows that there are signs and markers of the message in this film that are portrayed with humiliation, gender injustice, and unyielding attitudes by women who fight for their rights. There are also elements of women's emancipation, that women must be equal to men in any way, such as acting, behavior, speech, and mindset. Reject the notion that women are weak people who need protection from a man. Fil Bird's of Prey is a call for women's equality through film.